2016
DOI: 10.12662/2317-3076jhbs.v4i3.657.p160-165.2016
|View full text |Cite
|
Sign up to set email alerts
|

Características clínicas, prevalência e diagnóstico de vulvovaginites em ambulatório do interior do Rio Grande do Sul<br>Clinical characteristics and prevalence of vulvovaginitis in a clinic in the interior of the Rio Grande do Sul<br>doi:10.12662/2317-3076jhbs.v4i3.657.p160-165.2016

Abstract: Introdução:  As vulvovaginites são uma das principais queixas no atendimento rotineiro de ginecologia. O diagnóstico correto e o tratamento precoce dessas afecções são importantes além de prevenir possíveis repercussões no trato genital superior. Objetivo: Conhecer as características clínicas e a prevalência das vulvovaginites. Metodologia: Estudo transversal de natureza exploratória e descritiva, de abordagem quantitativa sobre mulheres que foram atendidas na Unidade de Atendimento de um Ambulatório de Gineco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…According to Tabile et al (2016), his research analyzed a sample of 200 tests in the years 2014 and 2015 and his results showed a microorganism infections incidence order similar to that of this research, in his work virus presence analysis was not performed.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…According to Tabile et al (2016), his research analyzed a sample of 200 tests in the years 2014 and 2015 and his results showed a microorganism infections incidence order similar to that of this research, in his work virus presence analysis was not performed.…”
Section: Resultssupporting
confidence: 54%
“…The diagnosis classified as others, which is seen in Graph 2, refers to a result that differs from the others, as it alludes in some cases to the absence of cellularity in the analyzed samples, another object that fits this classification is when the cytology presents a large amount of red cells preventing adequate visualization of the cells and this usually happens when the woman is tested while menstruating, in this period of the cycle it is not recommended to collect the material to be analyzed, since it can interfere with the results, however, sometimes the gynecologist performs it anyway, in addition to what was previously written, there may be results that were disease (PID), sterility, infertility, and other complications (Tabile et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Due to the discomfort in the well-being and negative interference in the quality of life for women, the occurrence of VV can be considered a public health problem. 3 The etiological diagnosis of VV is made through anamnesis, which addresses the clinical history and information about sexual practices and behaviors, menstrual cycles, hygiene habits, medications in use, clinical gynecological examination, and sample collection for laboratory analysis. 4 Approximately 90% of the women presenting clinical signs of VVare due to an infection by agents of the vaginal microbiota itself, which arises when there is an imbalance in the genital microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Em mulheres saudáveis em idade reprodutiva, os Lactobacillus spp. são predominantes e promovem a manutenção da homeostase vaginal, por meio da produção de ácido láctico, peróxido de hidrogênio, bacteriocinas e de outras substâncias que impedem a colonização e o crescimento de microrganismos adversos, incluindo os responsáveis por infecções sexualmente transmissíveis (IST) 3,4 .…”
Section: Introductionunclassified